3-DIMENSIONAL LOCALIZATION OF ELECTRONS ON AG ISLANDS - Fauster, Thomas; et al. (Physical Review B, 1993)
Image states on Pd(111) with various coverages of Ag were investigated by two-photon photoemission spectroscopy for temperatures between 90 and 1300 K. The formation of three-dimensional islands, smooth layers, and surface alloys is identified. The transition from one-dimensional localization in front of the surface to, three-dimensional localization on top of Ag islands with diameters between 10 and 100 Angstrom is observed. The high-resolution spectroscopy of image states provides a new tool to study the growth mode, morphology, and island size distribution of ultrathin metal films.